Identification and Characterization of Plasmids and Genes from Carbapenemase-Producing Klebsiella pneumoniae in Makkah Province, Saudi Arabia - Rayan Y. Booq; Mohammed H. Abutarboush; Mohammed A. Alolayan; Abdulaziz A. Huraysi; Amjad N. Alotaibi; Maha I. Alturki; Maryam K. Alshammari; Abrar A. Bakr; Azzam A. Alquait; Essam A. Tawfik; Nasser B. Alsaleh; Fayez S. Bahwerth; et al. (MDPI AG, 2022)
Klebsiella pneumoniae (K. pneumoniae) is involved in several hospital and community-acquired infections. The prevalence of K. pneumoniae-producing-carbapenemase (KPC) resistance genes rapidly increases and threatens public health worldwide. This study aimed to assess the antibiotic resistance level of K. pneumoniae isolates from Makkah Province, Saudi Arabia, during the Islamic 'Umrah' ritual and to identify the plasmid types, presence of genes associated with carbapenem hydrolyzing enzymes, and virulence factors. The phenotypic and genotypic analyses based on the minimum inhibitory concentration (MIC), biofilm formation, PCR, and characterization of KPC-encoding plasmids based on the replicon typing technique (PBRT) were explored. The results showed that most isolates were resistant to carbapenem antibiotics and other antibiotics classes. This study identified sixteen different replicons of plasmids in the isolates and multiple genes encoding carbapenem factors, with blaVIM and blaOXA-48 being the most prevalent genes identified in the isolates. However, none of the isolates exhibited positivity for the KPC production activity. In addition, this study also identified six virulence-related genes, including kfu, wabG, uge, rmpA, fimH, and a capsular polysaccharide (CPS). Together, the data reported in this study indicate that the isolated K. pneumoniae during the pilgrimage in Makkah were all resistant to carbapenem antibiotics. Although the isolates lacked KPC production activity, they carried multiple carbapenem-resistant genes and virulence factors, which could drive their resistant phenotype. The need for specialized methods for KPC detection, monitoring the possibility of nosocomial transmission, and diverse therapeutic alternatives are necessary for controlling the spreading of KPC. This study can serve as a reference for clinicians and researchers on types of K. pneumoniae commonly found during religious gathering seasons in Saudi Arabia.